Analysis of Parenting Patterns and Parental Feeding Practies and Their Impact on The Nutritional Status of School-Aged Children - Atika Noviana; Dedy Purwito (UM Purwokerto Press, 2026)
Background: School-age children require adequate nutritional intake to support their growth and development as they approach adolescence. Effective parenting styles and parental feeding practices help reduce the risk of nutritional disorders and support the growth and development of school-age children. This study aims to identify the relationship between parenting styles and parental feeding practices on the nutritional status of school-age children. Methodology: This quantitative study employs a cross-sectional design. The sampling technique used is total sampling, with a total of 85 students and their parents. Data analysis was conducted using the Spearman Rank test. Results: The study found that 74.1% of the children had normal nutritional status. The most common parenting style was authoritative, practiced by 74.1% of the parents. The most frequently used feeding practice was the restriction dimension to control body weight, with an average of 15.38%. There was no significant relationship between parenting styles and nutritional status (r=0.223, p0.05). However, there was a significant relationship between parental feeding practices and the nutritional status of school-age children in the dimensions of environment (r=0.005, p0.05), food as a reward (r=0.003, p0.05), modeling (r=0.004, p0.05), and restriction to control body weight (r=0.001, p0.05) at SDN 3 and 4 Pliken Kembaran Banyumas. Conclusion: Parental feeding practices play a crucial role in improving the nutritional status of school-age children, which is essential for enhancing children's health status.